1994
DOI: 10.1190/1.1443648
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of 3-D structures in the Interpretation of transient electromagnetic sounding data

Abstract: The limitations of a standard 1-D inversion applied to multidimensional (synthetic) data are investigated. Simple correction procedures for interpreting field data distorted by 3-D structures are suggested. Two different transmitter/receiver configurations of the transient electromagnetic (TEM) sounding method are examined: a central loop configuration for the near zone (sometimes called short offset) and a fixed transmitter/moving receiver configuration for the far zone (long offset). The 3-D models are struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…deviations from one-dimensionality and layer boundaries being transition/gradient zones rather than sharp boundaries) then the estimated model uncertainties are too optimistic. Goldman et al (1994) showed that 3-D structures may cause artificial low resistivities at depth in 1-D inversion results. However, we consistently observe the low-resistive layer, which we interpret to reflect salt-water-saturated sediment, over the entire study area.…”
Section: Discussionmentioning
confidence: 97%
“…deviations from one-dimensionality and layer boundaries being transition/gradient zones rather than sharp boundaries) then the estimated model uncertainties are too optimistic. Goldman et al (1994) showed that 3-D structures may cause artificial low resistivities at depth in 1-D inversion results. However, we consistently observe the low-resistive layer, which we interpret to reflect salt-water-saturated sediment, over the entire study area.…”
Section: Discussionmentioning
confidence: 97%
“…One-dimensional modelling of TEM data in the influence of 2-or 3-D structures has been studied by several authors (Newman et al, 1986;Goldman et al, 1994;Danielsen et al, 2003). Most important for the buried valley problem are effects that prevail close to the valley walls.…”
Section: The Tem Methodsmentioning
confidence: 99%
“…Many researchers have questioned the adequacy of a 1-D interpretation of 2-D or 3-D structures, such as a buried valley (Newman et al, 1987;Goldman et al, 1994;Toft, 2001). To investigate whether a 1-D model assumption is sufficient to accurately recover the slope of a buried valley, an intensive modelling study was performed.…”
Section: Multi-dimensional Modellingmentioning
confidence: 98%